Allelic expression mapping across cellular lineages to establish impact of non‐coding SNPs - Veronique Adoue; Alicia Schiavi; Nicholas Light; Jonas Carlsson Almlöf; Per Lundmark; Bing Ge; Tony Kwan; Maxime Caron; Lars Rönnblom; Chuan Wang; Shu‐Huang Chen; Alison H Goodall; et al. (Molecular Systems Biology)
Abstract Most complex disease‐associated genetic variants are located in non‐coding regions and are therefore thought to be regulatory in nature. Association mapping of differential allelic expression (AE) is a powerful method to identify SNPs with direct cis‐regulatory impact (cis‐rSNPs). We used AE mapping to identify cis‐rSNPs regulating gene expression in 55 and 63 HapMap lymphoblastoid cell lines from a Caucasian and an African population, respectively, 70 fibroblast cell lines, and 188 purified monocyte samples and found 40–60% of these cis‐rSNPs to be shared across cell types. We uncover a new class of cis‐rSNPs, which disrupt footprint‐derived de novo motifs that are predominantly bound by repressive factors and are implicated in disease susceptibility through overlaps with GWAS SNPs. Finally, we provide the proof‐of‐principle for a new approach for genome‐wide functional validation of transcription factor–SNP interactions. By perturbing NFκB action in lymphoblasts, we identified 489 cis‐regulated transcripts with altered AE after NFκB perturbation. Altogether, we perform a comprehensive analysis of cis‐variation in four cell populations and provide new tools for the identification of functional variants associated to complex diseases.